Application of antimicrobial peptide mytichitin-CB in pork preservation during cold storage. (July 2021) - Meng, De-Mei; Sun, Sheng-Nan; Shi, Lin-Yue; Cheng, Lei; Fan, Zhen-Chuan
Abstract: The antibacterial peptide mytichitin-CB has been highly expressed in Pichia pastoris . In this study, we aim to investigate its potential for application in pork preservation. P. pastoris -derived mytichitin-CB exhibited broad and potent antibacterial activity against four common foodborne bacterial pathogens and two food spoilage bacteria of Pseudomonas spp. with low minimal inhibition concentrations of 0.23–1.24 μg/mL. Mytichitin-CB effectively suppressed the growth of the microﬂora and signiﬁcantly reduced the increases in pH, drip loss, total volatile basic nitrogen (TVB-N), and thiobarbituric acid reactive substances (TBARS) of fresh pork during storage at 4 °C. Consequently, the fresh pork maintained its desirable sensory properties. Mytichitin-CB could also effectively inhibit the growth of Staphylococcus aureus, Escherichia coli O157, and Pseudomonas fluorescens in a pork spoilage model. Combining mytichitin-CB with chitosan and nisin at the optimal proportion further enhanced the antibacterial activity and effects of food preservation on fresh pork, as evidenced by improved sensory properties, lowered drip loss and TVB-N production, and reduced change in pH during storage. However, combining these three agents failed to further increase antioxidant activity against lipid oxidation. Overall, the combination of 4 mg/L of mytichitin-CB with 10 g/L of chitosan incorporated with 300 mg/L of nisin exhibited the best performance in fresh pork preservation. The combined findings suggest that treatment with mytichitin-CB alone or in combination with chitosan and nisin has considerable potential in the preservation of fresh meat products to extend the shelf life and assure the quality and safety of meat. Highlights: P. pastoris -derived mytichitin-CB exhibited broad and potent antibacterial activity. Mytichitin-CB could effectively extend the shelf life of pork during storage. Mytichitin-CB could effectively reduce the bacterial count in pork spoilage model. Combined chitosan/nisin/mytichitin-CB had a synergistic bactericidal effect on pork. Combined chitosan/nisin/mytichitin-CB further improved preservative quality of pork.